2003
DOI: 10.1614/p2002-110
|View full text |Cite
|
Sign up to set email alerts
|

Postdispersal predation of giant ragweed (Ambrosia trifida) seed in no-tillage corn

Abstract: Giant ragweed seeds have high nutritional value, consisting of 47% crude protein and 38% crude fat, and may be an important food source for rodent and invertebrate populations in agricultural and early successional ecosystems. We investigated temporal patterns of postdispersal giant ragweed seed predation on the soil surface of a no-tillage cornfield as affected by involucre (seed dispersal unit) size and presence or absence of crop residue. Cage exclusion experiments indicated that rodents and invertebrates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
127
1
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(142 citation statements)
references
References 35 publications
(80 reference statements)
12
127
1
2
Order By: Relevance
“…Moles et al [46] gathering data from the published literature and field trials on survivorship through post-dispersal seed predation, found a weak positive correlation between seed mass and the percentage of seeds remaining after 24 hours of exposure to post-dispersal seed predators in some Australian sites, and no significant relationship across 280 species from the global literature. A study on temporal patterns of post-dispersal giant ragweed seed predation on the soil surface of a no-tillage corn field as affected by involucre size indicated that rodents and invertebrates were the principal predators of giant ragweed seed [47]. Rodents were the greatest predators of giant ragweed involucres during fall and winter with a preference for large seeds (>4.8-mm diameter), while during the rest of the year invertebrate predation, with a preference for small involucres (<4.8-mm diameter), dominates [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moles et al [46] gathering data from the published literature and field trials on survivorship through post-dispersal seed predation, found a weak positive correlation between seed mass and the percentage of seeds remaining after 24 hours of exposure to post-dispersal seed predators in some Australian sites, and no significant relationship across 280 species from the global literature. A study on temporal patterns of post-dispersal giant ragweed seed predation on the soil surface of a no-tillage corn field as affected by involucre size indicated that rodents and invertebrates were the principal predators of giant ragweed seed [47]. Rodents were the greatest predators of giant ragweed involucres during fall and winter with a preference for large seeds (>4.8-mm diameter), while during the rest of the year invertebrate predation, with a preference for small involucres (<4.8-mm diameter), dominates [47].…”
Section: Discussionmentioning
confidence: 99%
“…A study on temporal patterns of post-dispersal giant ragweed seed predation on the soil surface of a no-tillage corn field as affected by involucre size indicated that rodents and invertebrates were the principal predators of giant ragweed seed [47]. Rodents were the greatest predators of giant ragweed involucres during fall and winter with a preference for large seeds (>4.8-mm diameter), while during the rest of the year invertebrate predation, with a preference for small involucres (<4.8-mm diameter), dominates [47]. Even if not directly demonstrated by the present investigation, it is plausible that the different morphological features, observed for common and giant ragweed seeds, collected in no-tillage fields (AAR and ATSR) and in non-agricultural sites (AAS and ATS), were also selected by specific pre-and post-dispersal predation patterns occurring in different environments.…”
Section: Discussionmentioning
confidence: 99%
“…The eating of seeds by carabids (granivory) was first recorded more than 100 years ago (Forbes, 1883;Webster, 1900) and confirmed since by many authors (Burmeister, 1939;Lindroth, 1949;Burakowski, 1967;Johnson & Cameron, 1969;Kirk, 1972;Best & Beegle, 1977;Lund & Turpin, 1977;Luff, 1980;Kjellsson, 1985;Brust & House, 1988;Trautner et al, 1988;Manley, 1992;Goldschmidt & Toft, 1997;Jorgensen & Toft, 1997a, b;Zhang et al, 1997;Hartke et al, 1998;Harrison et al, 2003). Carabid granivory is thus a well established phenomenon (Allen, 1979;Hengeveld, 1980b;Luff, 1987;Lovei & Sunderland, 1996;Kromp, 1999;Tooley & Brust, 2002).…”
Section: Introductionmentioning
confidence: 85%
“…Modelling studies have indicated that 25-50% seed mortality is generally sufficient to stop or slow down the population growth of annual weeds . Field studies have demonstrated predation levels exceeding this intensity (Hulme, 1994;Harrison et al, 2003;Westerman et al, 2003b;Honek et al, 2005), but seed predation levels are highly variable.…”
Section: Introductionmentioning
confidence: 99%